Taylor rules for the euro area: the issue of real-time data - Dieter Gerdesmeier; Barbara Roffia (Deutsche Bundesbank, 2004)
Recently, a number of studies have made an attempt to deal with the key issue of the incompleteness of information available to the central bank when taking its monetary policy decisions. This study adds to this literature by tackling the problem with regard to the euro area. The analysis is based on the simplistic assumption of the central bank following a simple monetary policy rule ?-la-Taylor. Along the lines of work suggested by Orphanides, the study tries to assess whether estimates of reaction functions which are carried out using revised data for the euro area can convey a misleading message in terms of policy recommendations.
Keywords: F41; E58; 330; Taylor Rules; Reaction Functions; Monetary Policy; Euro Area; Real Time Data; Taylor-Regel; Geldpolitik; Europäische Wirtschafts- und Währungsunion; Reaktionsfunktion